Seventy‐MHz Ultrasound Detection of Early Signs Linked to the Severity, Patterns of Keratin Fragmentation, and Mechanisms of Generation of Collections and Tunnels in Hidradenitis Suppurativa. (9th November 2019) - Wortsman, Ximena; Calderon, Perla; Castro, Ariel
Abstract : Objectives: To test the capability of 70‐MHz ultrasound for detecting initial ultrasound signs of hidradenitis suppurativa (HS) linked to severity. Methods: A cross‐sectional study of the ultrasound images of patients with HS was conducted and compared with a healthy control group. Detection and identification of early subclinical ultrasound signs in the lesional and perilesional areas of the HS cases in comparison with the control group were performed. Statistical analyses included mean, dispersion measures, the Kruskal‐Wallis test, and bivariate and multivariate ordered logistic regression studies. Significance was assessed at P  < .05. Results: A total of 139 patients with HS met the criteria and showed abnormalities of the hair follicles such as a curved shape, ballooning, and protrusion into pseudocysts, collections, or tunnels (donor of keratin sign). Significant increases in the sizes of the hair follicles and hair shafts were found in HS cases. The following ultrasound signs were significantly linked to severity: a connecting band between the base of adjacent hair follicles (bridge sign), a fragment of the hair shaft extruding through a dilated hair follicle (sword sign), and retained cylindrical fragments of keratin in the dermis. Two patterns of fragmentation of the keratin were detected: multifragment and cylindrical. Conclusions: Ultrasound can detect early HS signs that are significantly linked to severity and 2 types of fragmentation of the keratin, which could support the generation and perpetuation of the fluid collections and tunnels. These ultrasound signs can help prompt diagnosis and management, the development and testing of medications, and the measure of treatment outcomes in HS.